2016
DOI: 10.1080/00952990.2016.1203926
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarette initiation among minority youth in the United States

Abstract: Odds of initiating e-cigarette use was highest among Hispanic youth. Among minority youth, e-cigarette initiation was associated with perceptions of harm and addiction potential, as well as exposure to e-cigarette advertising. Therefore, prevention efforts targeting minority youth who are at risk of becoming e-cigarette initiators may benefit by incorporating these factors into prevention campaigns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 23 publications
2
27
1
Order By: Relevance
“…5 The odds of taking up vaping are higher among minority youth in the United States, particularly Hispanics. 9 This trend is particularly worrisome because several longitudinal studies have shown that adolescents who use e-cigarettes are 3 times as likely to eventually become smokers of traditional cigarettes compared with adolescents who do not use ecigarettes. [10][11][12] If US youth continue smoking at the current rate, 5.6 million of the current population under age 18, or 1 of every 13, will die early of a smoking-related illness.…”
Section: ■ Youth At Riskmentioning
confidence: 99%
“…5 The odds of taking up vaping are higher among minority youth in the United States, particularly Hispanics. 9 This trend is particularly worrisome because several longitudinal studies have shown that adolescents who use e-cigarettes are 3 times as likely to eventually become smokers of traditional cigarettes compared with adolescents who do not use ecigarettes. [10][11][12] If US youth continue smoking at the current rate, 5.6 million of the current population under age 18, or 1 of every 13, will die early of a smoking-related illness.…”
Section: ■ Youth At Riskmentioning
confidence: 99%
“…18 Exposure to these advertisements increases intention to use e-cigarettes among adolescent nonusers. 19 It is associated with current e-cigarette use, 20 with increasing exposure being associated with increased odds of use. 21,22 The increased use of and exposure to e-cigarettes among youth, combined with dramatic increases in advertising, 23 have serious potential to undermine successful efforts to deglamorize, restrict, and decrease the use of tobacco products.…”
Section: E-cigarette Marketing Advertising and Salesmentioning
confidence: 99%
“…Latino white youth are more likely to experiment with tobacco products than non-Latino youth are (45)(46)(47)(48). Latino youth may have lower perceived harm of e-cigarettes relative to non-Latino white youth, which may increase their risk of initiation, experimentation, and continuation (49). Non-Latino white youth are experiencing a faster decline in smoking rates than ethnic minorities are, including Latino youth (50,51).…”
Section: Introductionmentioning
confidence: 99%
“…These observations are suggestive of a telescoping effect of tobacco use in Latino youth and other ethnic minorities. As a result of such vulnerability, despite a later smoking onset, Latino youth are more likely to show undesired tobacco outcomes and tobacco-related illnesses and chronic diseases (43,(45)(46)(47)(48)(49).…”
Section: Introductionmentioning
confidence: 99%